Insights into the fracture mechanisms and strength of amorphous and nanocomposite carbon - Fyta, Maria G.; Remediakis, Ioannis N.; Kelires, Pantelis C. (My University, 2006)
Tight-binding molecular dynamics simulations shed light into the fracture mechanisms and the ideal strength of tetrahedral amorphous carbon and of nanocomposite carbon containing diamond crystallites, two of the hardest materials. It is found that fracture in the nanocomposites, under tensile or shear load, occurs intergrain and so their ideal strength is similar to the pure amorphous phase. The onset of fracture takes place at weakly bonded sp3 sites in the amorphous matrix. On the other hand, the nanodiamond inclusions significantly enhance the elastic moduli, which approach those of diamond.
Keywords: Carbon; Computer simulation; Crystals; Diamonds; Molecular dynamics; Nanostructured materials; Fracture mechanics